ENVIRONMENTAL IMPACT OF THE USE OF ARTIFICIAL INTELLIGENCE IN HEALTH (International Seven Journal of Multidisciplinary, 2025)
Artificial intelligence (AI) has emerged as a tool for innovation in healthcare, redefining diagnosis, treatment, and hospital management. From algorithms that improve medical image analysis to clinical decision support systems, AI offers significant benefits in the efficiency and accuracy of healthcare services. However, the growing demand for AI requires computing infrastructure, supported by data centers that consume large amounts of energy and natural resources. These centers, responsible for training and operating models such as GPT-3, generate significant greenhouse gas emissions and require large volumes of water for cooling. In addition, the production of specialized hardware and the disposal of equipment intensify environmental challenges. Paradoxically, AI also offers solutions to climate problems, such as optimizing energy resources and predicting natural disasters. The objective of this manuscript is to explore this duality, analyzing the benefits of AI in healthcare and the environmental challenges. Furthermore, sustainable practices and emerging technologies seek a balance between technological advancement and environmental preservation.